Assembling Çatalhöyük (Leeds)
xi, 201 s.
Keywords: "Assembling Çatalhöyük, like archaeological remains, can be read in a number of ways. At one level the volume reports on the exciting new discoveries and advances that are being made in the understanding of the 9000 year-old Neolithic site of Çatalhöyük. The site has long been central to debates about early village societies and the formation of ‘mega-sites’ in the Middle East. The current long-term project has made many advances in our understanding of the site that impact our wider understanding of the Neolithic and its spread into Europe from the Middle East. These advances concern use of the environment, climate change, subsistence practices, social and economic organization, the role of religion, ritual and symbolism. At another level, the volume reports on methodological advances that have been made by team members, including the development of reflexive methods, paperless recording on site, the integrated use of 3D visualization, and interactive archives. The long-term nature of the project allows these various innovations to be evaluated and critiqued. In particular, the volume includes analyses of the social networks that underpin the assembling of data, and documents the complex ways in which arguments are built within quickly transforming alliances and allegiances within the team. In particular, the volume explores how close inter-disciplinarity, and the assembling of different forms of data from different sub-disciplines, allow the weaving together of information into robust, distributed arguments." --